Regional and bilateral agreements and a TRIPS-plus world : the Free Trade Area of the Americas (FTAA) - Vivas-Egui, David (Quaker United Nations Office GenevaCH, 2003)
Provides an overview, based on Intellectual Property Rights negotiations in the Americas, of some of the implications of regional and bilateral TRIPS-plus agreements, for the current minimum standards under TRIPS.